2015
DOI: 10.1128/jvi.02898-14
|View full text |Cite
|
Sign up to set email alerts
|

A Cryo-Electron Microscopy Study Identifies the Complete H16.V5 Epitope and Reveals Global Conformational Changes Initiated by Binding of the Neutralizing Antibody Fragment

Abstract: Human papillomavirus 16 (HPV16) is a worldwide health threat and an etiologic agent of cervical cancer. To understand the antigenic properties of HPV16, we pursued a structural study to elucidate HPV capsids and antibody interactions. The cryo-electron microscopy (cryo-EM) structures of a mature HPV16 particle and an altered capsid particle were solved individually and as complexes with fragment of antibody (Fab) from the neutralizing antibody H16.V5. Fitted crystal structures provided a pseudoatomic model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
94
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(107 citation statements)
references
References 54 publications
13
94
0
Order By: Relevance
“…Subsequent structural studies have refined the C-terminal arm arrangement in HPV capsids (Fig. 8A) (9,17,18). Of the two types of available binding spaces (defined as type I and II in Results) for H16.U4 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent structural studies have refined the C-terminal arm arrangement in HPV capsids (Fig. 8A) (9,17,18). Of the two types of available binding spaces (defined as type I and II in Results) for H16.U4 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The centrifuged pellet was resuspended in 1 M NaCl-0.2 M Tris (pH 7.4). After CsCl gradient purification, the lower band was collected, concentrated, and dialyzed against phosphate-buffered saline (PBS), as described previously (9). The concentrated QV16 particles were applied to Formvarcoated copper grids, stained with 2% phosphotungstic acid, and analyzed for integrity and concentration on a JEOL JEM 1400 electron microscope.…”
Section: Preparation Of Hpv16 Quasivirus (Qv16)mentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of cryo-EM structures of Ab-virus complexes, Thouvenin and Hewat found that the fitting of Ab structures to the cryo-EM density was highly unreliable at partial occupancies of <50% and that the variation in density at regions with full occupancy was 515% (39), which suggests minimal and maximal limits for detectable partial occupancy of 15% and 85%, respectively. Previous cryo-EM studies of Ab-virus complexes have reported partial occupancies of 40-50% (40,41), whereas structures with partial occupancy of 20% do not reliably show density in icosahedral averaged structures (42,43). In the latter cases, low partial occupancy was detected based on the presence of a high-occupancy non-Fab-like overlap density of multiple overlapping low-density Fabs (42) or through the use of asymmetric reconstruction methods (43).…”
Section: Partial Occupancy and Heterogeneitymentioning
confidence: 99%